Implementasi Naïve Bayes pada Sistem Pakar untuk Deteksi Dini Penyakit Liver - Asri, Windi Fahmi; Sanglise, Marlinda; Suhendra, Christian Dwi (Faculty of Computer Science, University of Jember, 2024)
Liver health is very important for the human body. The liver as an organ that has the main task of neutralizing toxins in the body makes toxins that have been entering through our bodies from food or the environment can be neutralized by the liver. Based on the results of interviews conducted online to dr. Felix who works at Bhayangkara Hospital, one of the problems that occurs in the medical world is that people who are not medically trained if they experience symptoms of liver disease do not understand the ways to overcome them or the solution. If ignored, liver problems can get worse and more difficult to treat. Therefore, to overcome these problems, development is carried out by creating an expert system that can detect liver disease early by implementing the Naïve Bayes Method on the expert system. The expert system was built using the Rapid Application Development (RAD) development method. By making a design consisting of use cases, activities, class diagrams, database design and user interface design. Implementation in this expert system uses the PHP programming language and MySQL database. After the system is successfully created, the system is tested using the blackbox testing method which shows that the functionality of the expert system is running well and testing the user acceptance test (UAT) by distributing questionnaires to respondents to get the percentage of feasibility of 76.7% with a suitable category for use